Enhanced Barrier Property for Polyethylene Terephthalate–Polyethylene Naphthalate Copolymer by In Situ Polymerization with Graphene Oxide Nanosheets. Issue 10 (27th July 2022) - Quan, Li‐Jun; Liu, Zhen‐Guo; Zhang, Qiu‐Yu; Li, Zhong‐Ming; Chen, Yan‐Hui
Abstract: In this paper, a series of polyethylene terephthalate‐polyethylene naphthalate copolymer (PETN) composites with high oxygen barrier properties are prepared by introducing trace of graphene oxide (GO) during the in situ polymerization. The single‐layer GO nanosheets with large lateral size (≈1.8 µm) and abundant functional groups are prepared by a combination of chemical exfoliation and solvent exchange. During the in situ polymerization process, some surface region of GO is grafted by PETN molecular chains with the grafting rate being 80%, which enhanced the interfacial interaction between GO and PETN matrix. Furthermore, the ungrafting surface region of GO is thermally reduced to the complete graphene. Due to the in‐plane stacking of grafted GO and reduced GO, and the increased crystallinity of PETN matrix, the oxygen transport path of the PETN film is greatly prolonged, which endowed the PETN nanocomposite films with highly improved oxygen barrier performance. When the GO content is only 0.1 wt%, the oxygen permeability coefficient of the nanocomposite films is as low as 38.9 cc mil m −2 d −1 0.1 MPa −1, which is ≈4.5 times lower than that of the pure PETN film. This work provides a new idea for the preparation of polyester materials with high oxygen barrier performance. Abstract : A series of polyethylene terephthalate‐polyethylene naphthalate copolymer (PETN) composites with high oxygen barrier property are prepared by introducing trace of graphene oxide (GO) during the in situ polymerization. When the GO content is only 0.1 wt%, the oxygen permeability coefficient of the nanocomposite films is about 4.5 times lower than that of the pure PETN film.